Telomere Homeostasis and Senescence Markers Are Differently Expressed in Placentas From Pregnancies With Early- Versus Late-Onset Preeclampsia. (September 2019) - Farladansky-Gershnabel, Sivan; Gal, Hilah; Kidron, Debora; Krizhanovsky, Valery; Amiel, Aliza; Sukenik-Halevy, Rivka; Biron-Shental, Tal
Background: Early-onset preeclampsia (EOPE; <34 weeks' gestation) usually has more severe morbidity for the mother and fetus compared to late-onset preeclampsia (LOPE). Telomere homeostasis is disrupted in preeclampsia (PE) and senescence markers are increased. The pathophysiologic differences between early and LOPE are not fully unraveled yet. Methods: We studied placental biopsies from 7 pregnancies with EOPE, 6 pregnancies with LOPE, and 13 healthy gestational age-matched controls. Telomere length and aggregate formation were assessed using qualitative fluorescence in situ hybridization and electronic quantitative methods. Senescence markers were evaluated including senescence-associated heterochromatin foci, β-galactosidase (SAβ-Gal), and P16 staining, as was the expression of P16 complementary DNA (cDNA) using real-time quantitative polymerase chain reaction (RT-qPCR). Results: There were no differences in maternal age, gravidity, parity, body mass index, and mode of conception between the study and the control groups. The percentage of trophoblasts with short telomeres was higher in placental samples from EOPE (52.61% [12.27%]) versus LOPE (28.72% [10.14%]); both were higher compared to controls (7.53% [5.14%], P = .03). Aggregate formation was enhanced in EOPE (8.72% [2.49%]) compared to LOPE (4.54% [1.45%]); both were higher than in healthy controls (2.72% [1.08%], P = .03). Trophoblasts from EOPE versus LOPE were more likely to stain positive for SAβ-Gal and P16 compared to controls ( P < .001). P16 cDNA expression assayed by RT-qPCR was 7.51 times higher in EOPE compared to controls and 5.86 times higher than in LOPE. Conclusions: Impaired telomere homeostasis and senescence markers are more prominent in EOPE versus LOPE. These findings may contribute to our understanding of the pathophysiology and explain their different clinical presentations and outcomes.